Attack of the Bandit Cats : Geronimo Stilton #8 - Stilton, Geronimo; Wolf, Matt; Edizioni Piemme (New York Scholastic, 2004)
A ship of pirate cats kidnaps the mice who are searching for a legendary island covered in silver.
3.
007-010.
Keywords: Cats -- Fiction; Mice -- Fiction; Hot air balloons -- Fcition; Kidnapping -- Fiction